Pelatihan Teknik Aseptis Dalam Upaya Mengurangi Kontaminasi Mikroba Pada Petani Jamur Tiram Pleurotus ostreatus di Kecamatan Labakkang Kabupaten Pangkep : Aseptic Technique Training to Reduce Microbial Contamination for Pleurotus ostreatus Oyster Mushroom Farmers in Labakkang District, Pangkep Regency - Dwyana, Zaraswati; Haedar, Nur; Salam, Abdul; Abdullah, Asadi; Tuwo, Mustika (Sam Ratulangi University, 2024)
Community service has been carried out regarding aseptic technical training in an effort to reduce microbial contamination among Pleurotus ostreatus oyster mushroom farmers in Labakkang District, Pangkep Regency. The service was carried out in front of eastern mushroom farmers, groups of women and teenagers in Bara Batu village, Labakkang District, Pangkep Regency. In service activities, demonstrations and training are carried out on the use of aseptic methods in transferring fungal spores into mushroom bags, sanitation techniques for rooms and equipment used. The public is very enthusiastic about learning aseptic techniques in mushroom seed management to avoid rot damage to the mushroom growing media. This training activity was carried out face to face at the eastern mushroom business premises. This activity was attended by 50 people consisting of oyster mushroom farming groups, teenagers, Biology students from FMIPA Hasanuddin University. The method of service activities carried out is the delivery of scientific material and direct practice. From the results of the activities, training participants have knowledge about aseptic techniques to reduce contamination for oyster mushroom farmers so that the success rate of oyster mushroom harvesting can increase compared to before. ABSTRAK Telah dilakukan pengabdian masyarakat tentang pelatihan teknis aseptis dalam upaya mengurangi kontaminasi mikroba pada petani jamur tiram Pleurotus ostreatus di Kecamatan Labakkang Kabupaten Pangkep. Pengabdian dilakukan dihadapan petani jamur timur ,kelompok ibu-ibu dan remaja di desa Bara Batu Kec.Labakkang Kabupaten Pangkep. Dalam kegiatan pengabdian di lakukan demontrasi dan pelatihan penggunan metode aseptis dalam memindahkan spora jamur ke dalam baglog jamur, teknik sanitasi terhadap ruangan dan peralatan yang digunakan. Masyarakat sangat antusias untuk mempelajari Teknik aseptis didalam pengelolaan pembenihan jamur untuk menghindari kerusakan kebusukan dari media tumbuh jamur. Kegiatan pelatihan ini dilakukan dengan tatap muka langsung di tempat usaha jamur timur. Kegiatan ini diikuti oleh 50 orang yang terdiri dari kelompok tani jamur tiram , remaja , mahasiswa Biologi FMIPA Universitas Hasanuddin. Metoda kegiatan pengabdian yang dilakukan adalah penyampaian materi ilmiah dan praktek langsung. Dari hasil kegiatan peserta pelatihan mempunyai pengetahuan tentang Teknik aseptis untuk mengurangi kontaminasi pada petani jamur tiram sehingga tingkat keberhasilan panen jamur tiram dapat meningkat dari sebelumnya.